ANALISIS KEPEMIMPINAN CAMAT DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR CAMAT SAMBUTAN KOTA SAMARINDA - Syamsu Alam (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This article aim is to describe and analyze Head Leadership Role In Improving Employee Performance. Sources of data taken from the informant and key informants and supported by secondary data. Analysis of the data used is a model developed Flow Milles, Huberman and Saldana through stages. The results showed that the leadership role of Head Message from Samarinda applicative able to improve employee performance.Keyword : Employee Performance, Leadership